The importance of pregnant mother participation in Mama SASHA pregnant and lactating clubs in communities. - Wanjala, R.; Webb, A.; Grant, F.; Okuku, H.; Cole, D.; Low, Jan W.; Levin, C. (2014)
Antenatal clinics (ANCs) are critical for improving maternal nutrition and health knowledge. The Mama SASHA project in western Kenya delivers an orange flesh sweet potato intervention through ANC to improve the vitamin A status of women and children less than 2 years. A nested cohort study following women from pregnancy to 9 months postpartum was designed as an evaluation strategy for the Mama SASHA project. A survey was conducted at enrollment among 505 women, 10-24 weeks gestation attending first ANC clinic visit. Of the 505 enrolled women, 72% reported they had not yet received counseling from the nurse on exclusive breastfeeding for the first 6 months during the current pregnancy; over 90% reported not yet receiving counseling on when to initiate breast feeding, the importance of colostrum, when to initiate complementary feeding or how long to breast feed. 70 % of participants were multiparas (N=352) of whom 91% attended ANC during their previous pregnancy. Of these only 39% reported receiving information from the health facility on breast feeding during their previous pregnancy, 35% on how to eat during pregnancy, and 44% on how to feed young children. These findings highlight that ANC is lost opportunity for providing nutrition education and counseling. There is a significant need to strengthen nutritional counseling both at the ANC as well as through community based platforms such as pregnant and/or lactating clubs.